Electrochemical Impedance Spectroscopy for All‐Solid‐State Batteries: Theory, Methods and Future Outlook. Issue 11 (11th May 2021) - Vadhva, Pooja; Hu, Ji; Johnson, Michael J.; Stocker, Richard; Braglia, Michele; Brett, Dan J. L.; Rettie, Alexander J. E.
Abstract: Electrochemical impedance spectroscopy (EIS) is widely used to probe the physical and chemical processes in lithium (Li)‐ion batteries (LiBs). The key parameters include state‐of‐charge, rate capacity or power fade, degradation and temperature dependence, which are needed to inform battery management systems as well as for quality assurance and monitoring. All‐solid‐state batteries using a solid‐state electrolyte (SE), promise greater energy densities via a Li metal anode as well as enhanced safety, but their development is in its nascent stages and the EIS measurement, cell set‐up and modelling approach can be vastly different for various SE chemistries and cell configurations. This review aims to condense the current knowledge of EIS in the context of state‐of‐the‐art solid‐state electrolytes and batteries, with a view to advancing their scale‐up from the laboratory to commercial deployment. Experimental and modelling best practices are highlighted, as well as emerging impedance methods for conventional LiBs as a guide for opportunities in the solid‐state. Abstract : Materials to devices : Electrochemical impedance spectroscopy (EIS) is a powerful technique used in electrochemical research to interrogate materials, full cell devices and packs. This review summarizes the latest developments in EIS for sulfur, oxide and polymer solid‐state electrolytes in blocking electrode, symmetric and full cell configurations, with an outlook on how its applicability in this field can be improved.